Force design analysis of the Army aeromedical evacuation company: a quantitative approach. (January 2013) - Bastian, Nathaniel D; Fulton, Lawrence V; Mitchell, Robert; Pollard, Wayne; Wilson, Ronald
This study illustrates a new approach to conducting capabilities-based analysis by assessing the requirements and capabilities of Army aeromedical evacuation units. We conducted a DOTMLPF (doctrine, organization, training, maintenance, leadership, personnel, facilities) assessment to determine gaps in the current force structure and solutions for future force design. Specifically, this study tackles the following research questions. RQ1: What are the gaps in medical evacuation mission execution for current operations and operations involving geographically dispersed units? RQ2: What capabilities might mitigate these gaps by examining the design characteristics of DOTLMPF? Our research design involved primary collection of data from senior aviation and medical aviation leaders using structured and unstructured survey questions. Using a mixed-method approach, we addressed RQ1 using quantitative methods and RQ2 through qualitative analysis. The results of our study determined the current organizational problems within the Army aeromedical evacuation unit, which can be leveraged for the future joint force design for vertical lift. Our evaluation of medical evacuation DOTMLPF considerations provides a baseline for assessing future Army materiel solutions.